I like the way you move: how animate motion affects visual attention in early human infancy - Lunghi, Marco; Di Giorgio, Elisa (Frontiers in Neuroscience, 2024)
The ability to detect animates (as compared with inanimates) rapidly is advantageous for human survival. Due to its relevance, not only the adult human brain has evolved specific neural mechanisms to discriminate animates, but it has been proposed that selection finely tuned the human visual attention system to prioritize visual cues that signal the presence of living things. Among them, animate motion—i.e., the motion of animate entities -, is one of the most powerful cues that triggers humans’ attention. From a developmental point of view, whether such specialization is inborn or acquired through experience is a fascinating research topic. This mini-review aims to summarize and discuss recent behavioral and electrophysiological research that suggests that animate motion has an attentional advantage in the first year of life starting from birth. Specifically, the rationale underlying this paper concerns how attention deployment is affected by animate motion conveyed both by the movement of a single dot and, also, when the single dot is embedded in a complex array, named biological motion. Overall, it will highlight the importance of both inborn predispositions to pay attention preferentially to animate motion, mainly supported by subcortical structures, and the exposure to certain experiences, shortly after birth, to drive the cortical attentional visual system to become the way it is in adults.